Análise de sobrevida e prevalência de tumores de tireoide em um hospital de referência do Estado do Ceará - Silva, Carla Welch da (2022)
Thyroid cancer (TC) is a malignant neoplasm, being the most common in the head and neck region. It is classified in differentials, among them the most prevalent is the papillary, there are also few differentiated and undifferentiated. The increase in the incidence of TC already affects more than one million individuals in dozens of countries. In the United States, TC is increasing in risk faster than other cancers. According to Brazilian estimates, it is the fifth most frequent tumor in women in the Southeast and Northeast regions. The aim of the study was to analyze the prevalence and survival of malignant thyroid tumors in a tertiary hospital over a 15-year period. This is an observational, retrospective, longitudinal cohort epidemiological study of thyroids with a total sample of 4,050 cases of thyroid cancer from 2000 to 2014. Records of thyroid cancer in the aforementioned period were included and records without histological diagnosis were excluded. The collection occurred through the internal registry system of the Harold Juaçaba Diagnostic Center (HHJ) of the Hospital Instituto do Câncer do Ceará (ICC), the Brazilian Geography and Statistics database, and the Surveillance Information System database of the Quality of Water for Consumption Supply Coverage (SAA). An exploratory analysis by the description of the distribution of variables in the study population, stratified according to sex, race, histological type, year of diagnosis, municipal human development index (IDHM), region and federative unit of the patient, in addition to associating the prevalence of thyroid cancer with the level of fluoridation in the year 2014 of the municipalities of Ceará. Data were tabulated in Microsoft Excel and exported to SPSS software, in which analyzes were performed adopting a confidence of 95%. The Institute of Research and Economic Strategy of Ceará (IPECE) was used to create maps related to georeferencing. As a result, it was noted that the city of Fortaleza had the most cases, with 62.6% of all tumors evaluated and the highest density of cases per inhabitant of the city (9.49 cases/100,000 inhabitants). Females were the most prevalent with 85.4% (n=3,459) of the entire sample. The age distribution showed a gradual increase in prevalence up to the peak age group of 41-50 years (n=1003, 24.8% of cases) and a gradual reduction from this age onwards. Regarding the histological type, the most prevalent was papillary adenocarcinoma (n=3,743, 92.4%). Over 15 years of follow-up, the median survival was 90 months, and 94.8% of patients remained alive until the last visit. The relative rate of thyroid cancer was directly associated with a high survival rate (p=0.040). In multivariate analysis, year of diagnosis (p<0.001), female sex (p=0.003), level of education (p=0.027) and histological type of papillary adenocarcinoma (p<0.001) significantly reduced the risk of death, being age the factor directly associated with increased risk of death (p<0.001). The georeferencing of the density of thyroid cancer cases treated at the HHJ/ICC and the fluoride coverage in the state showed an association between the variables of water fluoridation rate and the number of patients with thyroid cancer in the municipalities of the center of the state. There was a high survival rate for thyroid cancer in the analyzed period.